(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: The main goal of the paper is to thematically cluster, identify, and present the most significant topics in the field of digitalization within small and medium enterprises. Additionally, the paper aims to propose guidelines for future research in this area. Methodology: In the paper, a bibliometric analysis of the literature was carried out on a sample of 285 articles with a special focus on keyword analysis, co-occurrence network analysis and trend topics analysis. Results: There has been a noticeable increase in interest in this topic since 2019, accompanied by a significant rise in the number of published articles and citations. Based on the analysis, five key thematic clusters were identified, which are related to the most frequently researched topics, and they are defined as follows: Digital technologies and Industry 4.0, Digital marketing and social media, COVID-19 and Innovation, Digital transformation, and Business models. Conclusion: The topic of digitalization in small and medium enterprises is gaining significant importance within the academic environment. This paper provides comprehensive guidelines covering methodological, practical, and thematic aspects, along with proposed research questions for future studies in this field.